2010
DOI: 10.1016/j.seizure.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and long term outcome in West syndrome: The clinical reality. A multicentre follow up study

Abstract: We systematically reviewed the files of 51 infants presenting with infantile spasms and hypsarrhythmia in order to study the initial treatment strategies and the long term outcome. 80% of the infants were classified as symptomatic. In the nine participating centres, different treatment protocols were used, but the large majority of the children received vigabatrin as first line treatment. Second line options included hormonal treatment, topiramate and valproate. The time to reach cessation of infantile spasms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 25 publications
(37 reference statements)
6
66
2
9
Order By: Relevance
“…Riikonen [4,5] reported that patients of WS with a favorable outcome had normal neurodevelopment before the onset of the spasms. Nearly all previous studies on this variable reported similar results [3,7,10,[21][22][23][24][25][26]. The presence of parental consanguinity and epilepsy in near relatives showed no significant effect on prognosis in this study.…”
Section: Neuro-developmental and Social Outcomessupporting
confidence: 84%
“…Riikonen [4,5] reported that patients of WS with a favorable outcome had normal neurodevelopment before the onset of the spasms. Nearly all previous studies on this variable reported similar results [3,7,10,[21][22][23][24][25][26]. The presence of parental consanguinity and epilepsy in near relatives showed no significant effect on prognosis in this study.…”
Section: Neuro-developmental and Social Outcomessupporting
confidence: 84%
“…This was greater than that in developed countries, which showed a lag time of 25 -45 days, but less than in other developing countries, at 7.9 months. [11,15] There was no correlation between the number of spasms per cluster or clusters per day and final neurological outcome in our study. The number of spasms at presentation was similar to that recorded in other studies.…”
Section: Discussioncontrasting
confidence: 61%
“…On sekiz aydan sonra nadir görülmekle birlikte, başlangıcı 4 yaş kadar geç olan olgular bildirilmiş-tir [5]. Önceki çalışmalarla benzer şekilde [10][11][12][13], çalışmamızda başlangıç yaşı ortalama 6.23 aydı.…”
Section: Discussionunclassified
“…Belirtilerin başlangıcından tanıya kadar geçen süre gelişmiş ülkelerde 1-1.5 ay arasında bildirilirken [10,12,13], gelişmekte olan ülkelerde 7.9 ay kadar uzun olabilmektedir [11]. Çalışmamızda ise bu süre 1.36 aydı.…”
Section: Discussionunclassified